Cooperation strategies among SMEs for implementing industry 4.0 - Julian Müller; Lukas Maier; Johannes Veile; Kai-Ingo Voigt (Digitalization in Supply Chain Management and Logistics: Smart and Digital Solutions for an Industry 4.0 Environment. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 23, 2017)
Industry 4.0 is expected to bring several conversions for industrial value creation, encompassing entire value-added networks. Small and medium-sized enterprises (SMEs), which play an important role for both the German as well as the European economy, struggle to integrate the concept of Industry 4.0 within their value creation. However, due to the high importance of SMEs for industrial value creation networks, their integration is essential to successfully establish Industry 4.0 across value chains. Several SMEs struggle to obtain the resources required for equipment and machinery or do not possess the required market shares or market access to establish new business models. Large enterprises are often seen as too powerful to be a partner for a SME. Nevertheless, cooperation strategies among SMEs may present a viable alternative to successfully implement Industry 4.0 across the value chain. In this context, literature lacks of a well-founded investigation of this topic. Therefore, this study attempts to close the present the present research gap. Due to the exploratory nature of the underlying topic, we conduct a multiple case study with 68 SMEs in Germany. This paper comes up with cooperation strategies and presents the interviewees' answers regarding potentials and challenges of common technology purchasing as well as for common business models. Subsequently, we present implications for both research and practice.
urn:nbn:de:gbv:830-88217599; 10419/209192; https://econpapers.repec.org/RePEc:zbw:hiclpr:23
Keywords: 650; industry 4.0; small and medium-sized enterprises; cooperation strategies; industrial internet of things